Application of newton Raphson and steepest descent method for precise positioning for mobile communications - Yamini Surya Teja, Ch; Vijay Gopal Reddy, B; Sri Harsha, S; Uday Kiran, K; S.Koteswara Rao, Dr (International Journal of Engineering and Technology, 2018)
GSM is a wireless networksystem. GSM mostly uses TDMA and most uses three digitalÂ wirelessmobile network technologies to compresses data, sends by using a channel along with other samples of data, in different time slots. It makes use of 900 to 1800MHz band frequency for transmission. Very accurate and exact wireless algorithms are difficult in all environmental conditions. Wireless communications use various parametric measurements to determine the sensor position. TOA is the time taken by the signal from source to reach the receiverâ€™s position. Newton Raphson method is an iterative numerical method uses partial derivatives of a functions or a system of equations in a suitable search direction. Newton Raphson consider two fundamental arguments: The first one is considering a good starting or initial point which is approximate to the solution and the secondary thing is to consider a distinguishable error which plays important role on approximation of the solution. In the present work, the Newton Raphson algorithm is implemented to obtain precise position of the receiver.